HUBUNGAN PROFESIONALISME GURU DAN KINERJA GURU SEKOLAH DASAR - Tuerah, Roos M. S.; Pusungula, Andre (DIKSAR : Jurnal Pendidikan Dasar, 2023)
The purpose of this study in general is to determine the relationship between teacher professionalism and the performance of elementary school teachers in West Kotamobagu District. This research uses a descriptive method which is a research with a quantitative approach. The quantitative approach in this study was to analyze questionnaire data, which was then analyzed using multiple linear regression formulas. The data collection technique used in this study uses the Likert scale model and uses an interval scale size, where the statements made by the researcher already have a score and all that remains is to be given a check mark in filling out the scale. The results of the study support the hypothesis that there is a relationship between teacher professionalism (X) and teacher performance (Y). This is indicated by the value of the regression coefficient X of 1.328. A significance value (sig) that is smaller than 0.05, namely 0.000 indicates that teacher professionalism has an influence on teacher performance. Where the null hypothesis (H0) is rejected and (H1) is accepted with a determination efficiency of 0.627 or 62.7%, it has a positive effect, meaning that the higher the teacher professionalism, the higher the teacher performance in West Kotamobagu sub-district. This presentation is very significant, although there are 37.3% which are other factors that affect variable Y and which are not examined in this study